Propuesta de un manual de funciones, valuación de puestos por puntos y reglamento de admisión y empleo para el talento humano de la empresa “Moreano Sánchez Rosa María” de la ciudad de Quevedo, provincia de Los Ríos - Velasco Barragán, Maribel Rocío (2015)
This research aims to propose an overall objective to propose a manual functions, job evaluation points and rules for admission and employment for the Company "Rosa María Sánchez Moreano" city of Quevedo To meet the main goal of this investigation methods such as inductive, analytical, deductive, synthetic, and techniques such as observation and interview, which allowed them to analyze the company and its organization in each of the posts have been applied and classify it, to do a survey was conducted on a sample of 222 employees, of which the results were removed. This work allowed analyze, evaluate and propose guidelines for Talent Company "Rosa María Sánchez Moreano" can anticipate, predict and ensure appropriate human talent to help meet the objectives of the company. The data obtained from the interview applied to the Manager and Lady a sample of 222 workers and employees allowed to know that the company "Moreano Rosa María Sánchez, has no manual functions, a valuation of positions for points and Admissions Regulation and employment. In the results and discussion, charts and graphs with data obtained from the surveys are set to perform a critical analysis of the current situation of the company, it was determined that 30% of employees have basic training and 25% have instruction superior, it was learned that 46% of employees have joined the company on the recommendation of family, without prior rules for admission and employment; likewise all respondents indicate that they have not received any manual or document relating to the work to be performed, 65% of respondents indicate that the position they play is not commensurate with their professional profile; and 100% of respondents also indicated that the company lacks a manual job classification, alarming situation because this will guide the management of human resources within the company, this is coupled with changes or adjustments made within the same to ensure compliance with all required standards for hiring and personnel management. As well as the results obtained enabled a valuation of positions per point based on the Position and the tasks entrusted to the company, for which purpose valuation factors such as Skills and Knowledge, Responsibility, Effort and conditions was first established work. Then the points are set for the grades and scores were given to each of the existing positions in the company performing a summation of each position and obtained the Assistant Manager got a score of 250, 250 Secretary General, Production Manager 340 , Financial manager 300, 250 Human Talent Manager, Marketing Manager 270, 140 Management Secretary, Head of Quality 210, 210 Agricultural Auditor, Financial Wizard 270, 320 Accountant, Head of human talent 230, 150 Operator, Assistant production310, 210 Security Guard, Driver 240 and the 140 workers were tabulated and mathematical formulas applied and finally the graph was performed for the realization of Pay Adjustment according to functions, knowledge, experience, initiative, personal responsibility, responsibility for team effort and risks in your workplace, resulting need the salary adjustment positions the agriculture Auditor, Accountant and Assistant Producer with 1.69% ; and should increase the salary the following staff: Quality Manager,Accountant,Talent human Manager, production assistant, Security Guard, and Driver. Finally a regulation of admission and employment that labor needs of the Company "Rosa María Sánchez Moreano" fits raised Also the conclusions and recommendations were determined